MODERNIZATION OF ISLAMIC EDUCATION LECTURE AT ISLAMIC HIGHER EDUCATION INSTITUTIONS IN CONTEMPORARY INDONESIA - Lubis, Rahmat Rifai; Hanafiah, Muhammad Ali; Dalimunthe, Rasyid Anwar; Rashed, Zetty Nurzuliana (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
This study aims to analyze the modernization of Islamic education literature at state Islamic universities in North Sumatra, in relation to efforts to increase students’ Islamic knowledge. This research follows a qualitative method, with a case study approach. The results revealed that the use of literature in the lecture process in general does not fully use Islamic-based literature. This can be seen from the Islamic education sources included in the lecturer’s course plan. It is found that there are three main efforts to modernize Islamic literature in the Islamic Education Study Program of PTKIN North Sumatra, namely (1) regulation, (2) development and updating references, literature content, and Islamicizing literature, as well as increasing the ability of lecturers and students, (3) innovation or the use of technology. Opportunities for modernization in increasing the scientific treasures of PAI (Islamic Education) study program students can be seen from the motivation, competence, resources and cooperation established. But there are also obstacles, namely internal obstacles, related to the lack of competence, attitude and campus facilities. External obstacles are related to the influence of journal trends and the dominance of western science. This research has novelty in the form of recommendations for a list of Islamic education lectures that are relevant in the modern era, guidelines for writing teaching materials based on Islamic lectures, and initiation of the formation of Islamic lectures research centres in Islamic universities.